The book of memory : a study of memory in medieval culture - Carruthers, Mary J. (Mary Jean), 1941- (Cambridge studies in medieval literature ;, 2008)
Mary Carruthers's classic study of the training and uses of memory for a variety of purposes in European cultures during the Middle Ages has fundamentally changed the way scholars understand medieval culture. This fully revised and updated second edition considers afresh all the material and conclusions of the first. While responding to new directions in research inspired by the original, this new edition devotes much more attention to the role of trained memory in composition, whether of literature, music, architecture, or manuscript books. The new edition will reignite the debate on memory in medieval studies and, like the first, will be essential reading for scholars of history, music, the arts and literature, as well as those interested in issues of orality and literacy (anthropology), in the working and design of memory (both neuropsychology and artificial memory), and in the disciplines of meditation (religion).